Dental considerations in obstructive sleep apnea - Retrieving current status - Sarita Shaukari; Raghu K Nandan; Meghana Gajavalli; Subi George (Wolters Kluwer Medknow Publications, 2021)
Obstructive sleep apnea (OSA) is a sleep disorder caused by partial or complete upper airway collapse with hallmark features of repetitive breathing cessation resulting in reduced oxygen saturation. India ranks third among countries worst hit by OSA. OSA is linked with elevated morbidity and mortality with various modifiable/nonmodifiable predisposing factors. Different medical approaches such as polysomnography, home sleep testing, dynamic magnetic resonance imaging, drug-induced sleep endoscopy, and neutrophil-to-lymphocyte ratio assist in diagnosis. Depending on disease severity, various treatment lines have been advocated, including behavioral modifications, continuous positive airway pressure, oral appliances (OAs), and surgical intervention. The role of pharmacotherapy in OSA remains controversial and demands extensive study. OA case selection and titration need to be done with utmost care. Definite protocols for the selection of suitable candidates for OA therapy need to be established. Various invasive and non-invasive surgical interventions such as bariatric surgeries, uvulopalatopharyngoplasty and Mandibular advancement appliances (MAA) have been advocated for OSA treatment. However, MMA requires a detailed diagnosis, including hard and soft tissue examination and an adequate recovery strategy to avoid any resulting adverse facial aesthetics. Implantable upper airway neurostimulators serve as a hope for newer therapeutic approaches. The need for the hour is a multidisciplinary solution to OSA.